Pengaruh Pajak, Ukuran Perusahaan, dan Profitabilitas terhadap Keputusan Perusahaan Melakukan Transfer Pricing - Olimsar, Fredy; Misidawati, Dwi Novaria; Marpaung, Rumintar J. H.; Setiawan, Heri; Utami, Eva Yuniarti (SAFE-Network, 2024)
This research aims to test and obtain empirical evidence regarding the influence of taxes, company size, probability on transfer pricing. This research uses a sample of subsector manufacturing companies... listed on the Indonesia Stock Exchange in 2019-2023. The sampling method used in this research is the purposive sampling method using SPSS for data analysis. This type of research is quantitative with 150 companies used as research samples with observations for 5 years, so the total research sample is 70 samples. The analysis technique used is regression. The results of this research show that simultaneously, tax, company size, and probability have an influence on companies carrying out transfer pricing.